Activation of annexin A1 signalling in renal fibroblasts exerts antifibrotic effects. (22nd September 2015) - Neymeyer, H.; Labes, R.; Reverte, V.; Saez, F.; Stroh, T.; Dathe, C.; Hohberger, S.; Zeisberg, M.; Müller, G. A.; Salazar, J.; Bachmann, S.; Paliege, A.
Abstract Aim The anti‐inflammatory protein annexin A1 (AnxA1) and its formyl peptide receptor 2 (FPR2) have protective effects in organ fibrosis. Their role in chronic kidney disease (CKD) has not yet been elucidated. Our aim was to characterize the AnxA1/FPR2 system in models of renal fibrosis. Methods Rats were treated with angiotensin receptor antagonist during the nephrogenic period (ARAnp) to induce late‐onset hypertensive nephropathy and fibrosis. Localization and regulation of AnxA1 and FPR2 were studied by quantitative real‐time PCR and double labelling immunofluorescence. Biological effects of AnxA1 were studied in cultured renal fibroblasts from AnxA1−/− and wild‐type mice. Results Angiotensin receptor antagonist during the nephrogenic period kidneys displayed matrix foci containing CD73+ fibroblasts, alpha‐smooth muscle actin (a‐SMA)+ myofibroblasts and CD68+ macrophages. TGF‐β and AnxA1 mRNAs were threefold higher than in controls. AnxA1 was localized to macrophages and fibroblasts; myofibroblasts were negative. FPR2 was localized to fibroblasts, myofibroblasts, macrophages and endothelial cells. AnxA1 and FPR2 immunoreactive signals were increased in the foci, with fibroblasts and macrophages expressing both proteins. AnxA1−/− fibroblasts revealed higher α‐SMA (sevenfold) and collagen 1A1 (Col1A1; 144‐fold) mRNA levels than controls. Treatment of murine WT fibroblasts with TGF‐β (22.5 ng mL 24 h−1) increased mRNA levels of α‐SMA (9.3‐fold) and Col1A1 (fourfold). These increases were greatly attenuated upon overexpression of AnxA1 (1.5‐ and 1.7‐fold, respectively; P < 0.05). Human fibroblasts reacted similarly when receiving the FPR2 inhibitor WRW4. Conclusion Our results demonstrate that AnxA1 and FPR2 are abundantly expressed in the renal interstitium and modulate fibroblast phenotype and extracellular matrix synthesis activity.